Research review and transcriptomic insights into Benzalkonium chloride inhalation and disease association - Jun Woo Kim; Min Seok Kim; Ha Ryong Kim (Ecotoxicology and Environmental Safety)
The widespread use of disinfectants, particularly during the coronavirus disease (COVID-19) pandemic, has significantly increased human exposure to biocides, raising concerns about their potential health risks, especially when inhaled. Benzalkonium chloride (BKC), a quaternary ammonium compound commonly used as a disinfectant and preservative, is a notable example because it is frequently used in household products and medical settings. Despite its broad usage, limited research has been conducted on the respiratory and systemic toxicities of BKC. Here, we conducted a research review of the literature on the respiratory toxicity of BKC. This research review suggests that, while current studies imply that BKC may induce respiratory diseases, the evidence remains insufficient. We employed an aerosol exposure model using primary bronchial epithelial cells to simulate inhalation exposure to BKC in humans. Transcriptomic analysis was performed to identify differentially expressed genes (DEGs) associated with toxicological pathways, including endoplasmic reticulum (ER) stress, apoptosis, mitochondrial dysfunction, and epithelial-mesenchymal transition (EMT). The results were integrated with gene-disease association databases to explore the links between BKC exposure and respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), and pulmonary fibrosis. Our study also examined the systemic effects of BKC by analysing the secreted proteins, suggesting possible cardiovascular implications. These findings highlight the need for further research on the health impacts of BKC, particularly its long-term effects, and underscore the importance of regulating its use to minimise the potential health risks associated with exposure via inhalation.